Peran dan Tantangan International Criminal Court (ICC) dalam Percobaan Perdamaian Konflik Israel-Palestina - Zaenudin, Zaenudin; Kamungnay, Adinda Santi; Febriani, Silfiana (Lembaga Yasin AlSys, 2025)
The International Criminal Court (ICC) plays a strategic role in upholding international law, particularly in addressing grave crimes such as genocide, crimes against humanity, and war crimes. In the context of the Israel-Palestine conflict, the ICC serves as an independent body offering hope to Palestine in seeking accountability for alleged human rights violations committed by Israel. This study analyzes the ICC’s role in the conflict and identifies the challenges it faces. The findings reveal that the ICC’s jurisdiction, as stipulated by the Rome Statute, encounters significant obstacles, particularly as Israel has not ratified the Rome Statute and firmly rejects the ICC’s authority. Conversely, Palestine, a member of the ICC since April 2015, has sought to utilize international legal mechanisms to pursue justice. The study concludes that while the ICC has considerable potential to enforce justice, legal and political challenges such as the refusal of cooperation by accused parties and the complex geopolitical dynamics limit its effectiveness. This research provides critical insights into the ICC’s role and challenges in administering justice in conflict zones, as well as its contribution to peace efforts in Israel and Palestine.